The once and future Canadian democracy : an essay in political thought - Ajzenstat, Janet, 1936- (McGill-Queen's University Press, 2003)
To revitalize politics we need to abandon the idea that ideologies evolve from "right" to "left", from conservatism to socialism, and look at our political differences in terms of the distinction, more familiar in the arts, between classicism and romanticism. She argues that by abandoning our current modes of debate and rediscovering the Enlightenment liberalism that is an enduring part of our political tradition we will help to recreate Canada as a place of debate on fundamentals, not one in which a monolithic definition of identity answers all questions in advance.